2019
DOI: 10.1002/smtd.201900031
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Range HS‐AFM Imaging of DNA Self‐Assembly through In Situ Data‐Driven Control

Abstract: Understanding hierarchical self‐assembly of biological structures requires real‐time measurement of the self‐assembly process over a broad range of length‐ and timescales. The success of high‐speed atomic force microscopy (HS‐AFM) in imaging small‐scale molecular interactions has fueled attempts to introduce this method as a routine technique for studying biological and artificial self‐assembly processes. Current state‐of‐the‐art HS‐AFM scanners achieve their high imaging speed by trading achievable field of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…A low-pass filter setting between 10-100 kHz was implemented after the pre-amplifier (Stanford SR560). A custom SICM controller (Supplementary Notes 1) consisting of a data-driven scan engine 7,42 and adaptive hopping mode was implemented in LabVIEW on a NI USB-7856R OEM R Series (National Instruments, Austin, TX, USA) in the framework of a home-built extensible high-performance scanning probe controller.…”
Section: Methodsmentioning
confidence: 99%
“…A low-pass filter setting between 10-100 kHz was implemented after the pre-amplifier (Stanford SR560). A custom SICM controller (Supplementary Notes 1) consisting of a data-driven scan engine 7,42 and adaptive hopping mode was implemented in LabVIEW on a NI USB-7856R OEM R Series (National Instruments, Austin, TX, USA) in the framework of a home-built extensible high-performance scanning probe controller.…”
Section: Methodsmentioning
confidence: 99%
“…In data-driven control strategies such as the ones developed in one of our labs [128] the traditional optimization-based solvers can be replaced by machine learning, thereby ensuring faster and more accurate tracking of the sample without exciting unwanted resonances.…”
Section: Enhancing Speed Of Image Acquisitionmentioning
confidence: 99%
“…Machine learning techniques, in general, can be used to increase the image acquisition speed, by reducing the number of data points that need to be acquired, as discussed earlier. In data-driven control strategies such as the ones developed in one of our labs [ 128 ] the traditional optimization-based solvers can be replaced by machine learning, thereby ensuring faster and more accurate tracking of the sample without exciting unwanted resonances.…”
Section: Reviewmentioning
confidence: 99%
“…To a large extent, the structure of G‐quadruplex nucleic acid has high thermodynamic stability under close physiological conditions. [ 126–129 ] Biffi et al. reported that G‐quadruplex nucleic acid can be engineered to produce and apply structure‐specific antibodies, which can quantitatively deliver the structure of DNA G‐quadruplex in human cells.…”
Section: Smfs Study On Intra‐ or Intermolecular Interactionsmentioning
confidence: 99%
“…To a large extent, the structure of G-quadruplex nucleic acid has high thermodynamic stability under close physiological conditions. [126][127][128][129] Biffi et al reported that G-quadruplex nucleic acid can be engineered to produce and apply structure-specific antibodies, which can quantitatively deliver the structure of DNA G-quadruplex in human cells. [130] They found that the small molecule ligand captures the cell structure and accurately locates the G-quadruplex structure map through the genome sequence.…”
Section: G Quadruplex and Internal Molecular Interactionsmentioning
confidence: 99%